A polyformal semi-solid lithium ion battery and a preparation method and application thereof
Patent Information
- Application Number
- CN202210834046.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-07-14
AI Technical Summary
采用含液态电解质组分的凝胶聚合物电解质能在一定程度上提高电池的安全性能,但电解质由液态变成凝胶后,电解质的粘度增加,离子电导率会明显降低,导致电池内阻增加,影响电池的循环性能
[0037]申请人研究意外发现,在不减少液态电解液注入量的前提下,把液态电解液的部分溶剂用三聚甲醛代替,在电池化成过程中使三聚甲醛在电池内原位聚合形成不溶于液态组分的聚甲醛,形成聚甲醛半固态锂离子电池。三聚甲醛聚合之后,电池内可挥发的液态组分含量显著降低,且液态组分被固定在聚甲醛的框架中,从而提高电池的安全性能。本发明电解液中的三聚甲醛聚合形成聚甲醛半固态锂离子电池后,其内阻没有显著增加,且电池的长期循环性能略有提升。具体而言:
Smart Images

Figure CN117438634B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion solid-state batteries, and relates to a polyoxymethylene semi-solid lithium-ion battery, its preparation method, and its application. Background Technology
[0002] In recent years, human activities have led to a sharp decline in fossil fuel resources, with some energy sources nearing depletion. The resulting environmental degradation and irrational resource utilization have had a significant impact on human life and production. To meet people's growing material and cultural needs while ensuring safe and sustainable production and living, the development of a new, safe, and environmentally friendly energy system is therefore urgently needed.
[0003] Lithium-ion batteries are widely used not only in portable electronic devices (such as digital cameras and portable computers) but also in power tools and electric vehicles. However, safety issues such as combustion and explosion have hindered the further development of lithium-ion batteries. These safety concerns mainly involve the dissolution of positive and negative electrode materials, membrane puncture, and the evaporation and leakage of the liquid electrolyte. Currently, commonly used liquid electrolytes are all prepared from volatile liquids and participate in all electrochemical reactions. Leakage of volatile electrolytes, battery flammability, and overpotential decomposition severely limit the safety performance of lithium-ion batteries.
[0004] To overcome the leakage problems of liquid electrolytes, researchers have begun to study inorganic solid electrolytes, solid polymer electrolytes, and organic / inorganic composite electrolytes as alternatives. However, due to issues such as low ionic conductivity or high interfacial impedance, all-solid-state batteries using all-solid-state electrolytes have not yet achieved a breakthrough, thus remaining far from practical application. For a considerable period, liquid electrolytes will likely remain the best choice for stable cycling of lithium-ion batteries. Using gel polymer electrolytes containing liquid electrolyte components can improve battery safety to some extent, but the viscosity of the electrolyte increases after it changes from liquid to gel, significantly reducing ionic conductivity and leading to increased internal resistance, thus affecting the battery's cycle performance. Summary of the Invention
[0005] To improve the above-mentioned technical problems, the present invention provides a polymerizable electrolyte comprising an electrolyte lithium salt, an electrolyte solvent, trioxymethylene, and a polyoxymethylene stabilizing additive.
[0006] According to an embodiment of the present invention, the polymerizable electrolyte has an ionic conductivity of 3.0-12.0 mS / cm. -1 An example is 3.0 mS cm -1 4.0mS cm -1 6.0 mS cm-1 8.0mS cm -1 10.0mS cm -1 12.0mS cm -1 .
[0007] According to embodiments of the present invention, the electrolyte lithium salt includes, but is not limited to, one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiTFSI, LiFSI, LiBOB, LiPO2F2, and LiDFOB.
[0008] Preferably, the molar concentration of the electrolyte lithium salt in the polymerizable electrolyte is 0.5-2.0 mol / L (M), more preferably 0.8-1.2 M, and exemplary concentrations are 0.5 M, 0.8 M, 1.0 M, 1.2 M, 1.5 M, and 2.0 M.
[0009] According to embodiments of the present invention, the electrolyte solvent includes, but is not limited to, one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), 1,3-dioxane (DOL), dimethyl ethylene glycol (DME), γ-butyrolactone (γ-BLO), tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether. The electrolyte solvent is used to dissolve the sodium electrolyte salt.
[0010] According to an embodiment of the present invention, the polymerizable electrolyte may optionally include electrolyte additives for forming a solid electrolyte interface film on the electrode surface to improve the cycle performance of the battery.
[0011] Preferably, the electrolyte additive includes, but is not limited to, at least one of vinylene carbonate (VEC), fluoroethylene carbonate (FEC), propane sulfonate lactone (PS), 3-fluoropropane sulfonate lactone (FPS), and 1,3-propenylpropane sulfonate lactone (PES).
[0012] Preferably, the electrolyte additive is present in a polymerizable electrolyte at a content of 1.0-7.0 wt%, more preferably 3.0-5.0 wt%, with examples being 1.0 wt%, 2.0 wt%, 3.0 wt%, 5.0 wt%, and 7.0 wt%.
[0013] According to an embodiment of the present invention, the content of paraformaldehyde in the polymerizable electrolyte is 5.0-60.0 wt%, preferably 15.0-30.0 wt%; exemplary values are 5.0 wt%, 10.0 wt%, 15.0 wt%, 20.0 wt%, 30.0 wt%, 40.0 wt%, and 60.0 wt%.
[0014] According to embodiments of the present invention, the polyoxymethylene stabilizing additive includes, but is not limited to, at least one of dioxolane compounds, compounds with monoepoxy functional groups, and compounds with polyepoxy functional groups. It is used to modify the main chain structure of polyoxymethylene, thereby improving its thermal decomposition temperature and high-temperature stability.
[0015] Preferably, the dioxolane compound is selected from, for example, DOL, 4-methyl-1,3-dioxolane, etc.
[0016] Preferably, the compound with the monoepoxy functional group is selected from, for example, propylene oxide (PO), epichlorohydrin (ECH), epibromopropane, 1,2-epoxyhexane, propyl ethylene oxide, phenyl glycidyl ether, methyl 2,3-epoxypropionate, ethyl 2,3-epoxypropionate, benzyl glycidyl ether, 2-biphenyl glycidyl ether, etc.
[0017] Preferably, the compound with the polyepoxy functional group is selected from, for example, 1,2,7,8-diepoxyoctane, dicyclopentadiene epoxide, 1,5-hexadiene diepoxide, vinylcyclohexene dioxide, neopentyl glycol diglycidyl ether, ethylene glycol glycidyl ether, bisphenol A diglycidyl ether, glycerol triglycidyl ether, pentaerythritol glycidyl ether, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexyl carboxylate, etc.
[0018] According to an embodiment of the present invention, the content of the polyoxymethylene stabilizing additive relative to trioxymethylene is 0.5-7.0 wt%, preferably 1.0-4.0 wt%, and exemplary values are 0.5 wt%, 1.0 wt%, 2.0 wt%, 4.0 wt%, 5.0 wt%, and 7.0 wt%.
[0019] The present invention also provides a semi-solid polymer electrolyte, which is prepared from the above-mentioned polymerizable electrolyte.
[0020] According to an embodiment of the present invention, the ionic conductivity of the semi-solid polymer electrolyte is 0.5-11.0 mS / cm. -1 An example is 0.5mS cm -1 1.0mS cm -1 3.0mS cm -1 4.0mS cm -1 6.0 mS cm -1 8.0mS cm -1 10.0mS cm -1 11.0mS cm -1 .
[0021] The present invention also provides a method for preparing the above-mentioned semi-solid polymer electrolyte, comprising sealing and placing the above-mentioned polymerizable electrolyte at 20-65°C for more than 5 hours, so that the transparent liquid electrolyte is transformed into a white polyoxymethylene-containing semi-solid polymer electrolyte.
[0022] The present invention also provides the application of the above-mentioned semi-solid polymer electrolyte in energy storage devices; preferably, the energy storage device is a battery; more preferably, it is a lithium-ion battery, and even more preferably, it is a polyoxymethylene semi-solid lithium-ion battery.
[0023] The present invention also provides a polyoxymethylene semi-solid lithium-ion battery containing the above-mentioned semi-solid polymer electrolyte.
[0024] According to an embodiment of the present invention, the cell of the polyoxymethylene semi-solid lithium-ion battery contains 0.5-10.0 wt% trioxymethylene. Preferably, the content of trioxymethylene is 1.5-6.0 wt%, with examples being 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, 5.0 wt%, 6.0 wt%, and 10.0 wt%.
[0025] According to an embodiment of the present invention, the polyoxymethylene semi-solid lithium-ion battery can be a square stacked battery or a cylindrical wound battery.
[0026] According to an embodiment of the present invention, the internal resistance of the polyoxymethylene semi-solid lithium-ion battery increases by no more than 50%, preferably no more than 30%, more preferably no more than 10%, and exemplary no more than 5%, compared with the same type of cell containing the same mass of ordinary electrolyte.
[0027] According to an embodiment of the present invention, the polyoxymethylene semi-solid lithium-ion battery further comprises a negative electrode and / or a positive electrode.
[0028] Preferably, the positive electrode active material used in the positive electrode can be one of transition metal oxide materials or conversion-type positive electrode materials.
[0029] For example, the transition metal oxide material is selected from one, two or more of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary cathodes (such as 532, 622, 811, etc.), nickel-cobalt-aluminum ternary cathodes, lithium manganese oxide, lithium-rich manganese-based cathodes, etc.
[0030] For example, the conversion cathode material is selected from one, two or more of sulfur cathodes, iron fluoride cathodes, etc.
[0031] Preferably, the negative electrode can be made of carbon materials (such as natural graphite, artificial graphite, mesophase carbon microspheres (MCMB), soft carbon (such as coke), hard carbon, etc.), or non-carbon negative electrode materials (such as lithium titanate, silicon-based materials and their composites, nitrides, tin-based materials, etc.), or it can be a composite negative electrode of carbon materials and non-carbon materials (such as graphite doped with silicon, graphite doped with silicon suboxide composite negative electrode, etc.).
[0032] The present invention also provides a method for preparing the above-mentioned polyoxymethylene semi-solid lithium-ion battery, comprising injecting the above-mentioned polymerizable electrolyte into the cell of a lithium-ion battery to prepare the polyoxymethylene semi-solid lithium-ion battery.
[0033] Alternatively, during the preparation of lithium-ion battery electrodes, 0.5-10 wt% of trioxymethylene relative to the positive and / or negative active materials is added, and then the polymerizable electrolyte is injected into the lithium-ion battery cell to prepare the polyoxymethylene semi-solid lithium-ion battery.
[0034] According to an embodiment of the present invention, the preparation method of the polyoxymethylene semi-solid lithium-ion battery includes the following steps: injecting the polymerizable electrolyte into the cell of a lithium-ion battery, evacuating and allowing it to stand, sealing it under vacuum, and then allowing it to stand until the electrolyte is fully impregnated. The cell is then allowed to stand before normal formation to allow the trioxymethylene to polymerize and form a semi-solid lithium-ion battery. The battery is then transferred to the normal formation process to obtain the polyoxymethylene semi-solid lithium-ion battery. Preferably, the temperature for standing before normal formation is 25-65℃, more preferably 40-50℃; the standing time before normal formation is greater than 5 hours, preferably 24-48 hours.
[0035] Alternatively, during the preparation of lithium-ion battery electrodes, 0.5-10 wt% of trioxymethylene relative to the positive and / or negative electrode active materials is added. The polymerizable electrolyte of this trioxymethylene is then injected into the lithium-ion battery cell. After vacuum sealing, the cell is left to stand until the electrolyte fully impregnates and dissolves the trioxymethylene from the positive and / or negative electrodes. Before normal formation, the cell is allowed to stand, allowing the trioxymethylene to polymerize and form a semi-solid lithium-ion battery. The battery is then transferred to the normal formation process to obtain a polyoxymethylene semi-solid lithium-ion battery. Preferably, the temperature for standing before normal formation is 25-65°C, more preferably 40-50°C; the standing time before normal formation is greater than 5 hours, preferably 24-48 hours.
[0036] Beneficial effects of the present invention
[0037] The applicant's research unexpectedly revealed that, without reducing the amount of liquid electrolyte injected, partially replacing the solvent in the liquid electrolyte with trioxymethylene (TOM), the TOM polymerizes in situ within the battery during battery formation to form polyoxymethylene (POM), which is insoluble in the liquid components, thus creating a POM semi-solid-state lithium-ion battery. After TOM polymerization, the content of volatile liquid components within the battery is significantly reduced, and the liquid components are fixed within the POM framework, thereby improving battery safety performance. After the TOM in the electrolyte of this invention polymerizes to form a POM semi-solid-state lithium-ion battery, its internal resistance does not increase significantly, and the long-term cycle performance of the battery is slightly improved. Specifically:
[0038] 1. This invention provides a polymerizable electrolyte system containing paraformaldehyde, its preparation method, and its application. During research, the applicant unexpectedly discovered that after adding paraformaldehyde to a liquid electrolyte and polymerizing it, the electrolyte does not separate into layers; instead, the liquid components are adsorbed between the polyformaldehyde crystals to form a semi-solid polymer electrolyte. The ionic conductivity of the semi-solid polymer electrolyte of this invention is comparable to that of the liquid electrolyte.
[0039] 2. This invention provides a method and application for preparing a semi-solid-state lithium-ion battery using in-situ solid-state integrated technology. The method involves adding a polymerizable electrolyte containing trioxymethylene (TOM) to a lithium-ion battery at the normal electrolyte injection rate, or dissolving TOM from the positive and / or negative electrode sheets into the electrolyte injected into the cell. Before formation, the TOM is polymerized, and after normal formation, a semi-solid-state lithium-ion battery can be prepared. The in-situ solid-state integrated technology integrates the positive electrode, negative electrode, and separator into a single unit, stabilizing the electrode structure and mitigating the shedding of active electrode materials due to volume expansion and contraction during cycling, thereby improving battery consistency and stability. Simultaneously, the battery's internal resistance does not increase significantly, and its cycle performance is comparable to that of a lithium-ion battery injected with the same mass of ordinary liquid electrolyte without degradation. The TOM semi-solid-state lithium-ion battery of this invention significantly reduces the content of volatile liquid components, thus achieving both stable cycle performance and higher safety performance.
[0040] 3. In this invention, when a semi-solid lithium-ion battery is prepared using in-situ solid-state integrated technology, the polymerizable electrolyte containing trioxymethylene polymerizes in the micropores of the separator. The surface of the separator and the micropores contain polyoxymethylene with high thermal stability, which significantly reduces the thermal shrinkage performance of the separator. Therefore, it has higher thermal stability and can better prevent internal short circuits in the battery, thereby further improving the safety of the battery.
[0041] 4. The process of preparing semi-solid lithium-ion batteries using in-situ solid-state integrated technology is compatible with existing liquid lithium-ion battery processes. It is achieved by placing the solid-state integrated process of trioxymethylene polymerization at a certain temperature and letting it stand for a period of time before the battery is normally formed. The subsequent formation and cycling processes are exactly the same as existing processes, so it is easy to realize the industrial production of high-safety semi-solid lithium-ion batteries. Attached Figure Description
[0042] Figure 1 This is an optical photograph of the polyoxymethylene semi-solid polymer electrolyte in Example 1.
[0043] Figure 2 The image shows electron microscope (EM) images of the internal electrodes of the polyoxymethylene semi-solid lithium-ion battery after disassembly in Example 2.
[0044] Figure 3 This is an electron microscope image of the separator surface after disassembly of the polyoxymethylene semi-solid lithium-ion battery in Example 2.
[0045] Figure 4 The first charge-discharge curves are shown for the polyoxymethylene semi-solid lithium-ion battery prepared in Example 2 and the ordinary liquid lithium-ion battery in Comparative Example 1.
[0046] Figure 5 The graph shows the cycle performance results of the polyoxymethylene semi-solid lithium-ion battery prepared in Example 2 and the ordinary liquid lithium-ion battery in Comparative Example 1.
[0047] Test methods
[0048] The ionic conductivity in the following embodiments and comparative examples of the present invention was tested using an Interface 1000 electrochemical workstation from Gamry Corporation, with a scan frequency of 1.0 Hz to 100 kHz.
[0049] The battery internal resistance in the following embodiments and comparative examples of the present invention was tested using an HK-3560 precision internal resistance tester.
[0050] The battery cycle performance in the following embodiments and comparative examples of the present invention was tested using the Blue Electric CT2001A battery testing system.
[0051] The method for measuring the polyoxymethylene content in the disassembled battery cells is as follows:
[0052] (1) Disassemble the prepared polyoxymethylene semi-solid sodium-ion battery, weigh the cell mass, and record the cell mass as W1.
[0053] (2) Open the battery cell and place it in a tetrahydrofuran solution equivalent to 10 times the mass of W1. Stir thoroughly, then filter to remove the binder polyvinylidene fluoride (PVDF) from the positive electrode, the binder styrene-butadiene rubber (SBR) from the negative electrode, lithium salt, electrolyte solvent, and additives. Dry and weigh. Repeat this step 2-3 times until the weight deviation is less than 5%.
[0054] (3) Place the residue in deionized water equivalent to 10 times the mass of W1 and stir thoroughly. Then filter to remove the thickener carboxymethyl cellulose (CMC), dry and weigh. Repeat this step 2-3 times until the weight deviation is less than 5%, and record the mass of the residue as W2.
[0055] (4) Place the residue in 5 times the mass of W2 in hexafluoroisopropanol and stir thoroughly. Then filter to remove the polyoxymethylene, dry and weigh. Repeat this step 2-3 times until the weight deviation is less than 5%, and record the mass of the residue as W3.
[0056] (5) The method for calculating the polyoxymethylene content (x%) in the disassembled battery cell is as follows:
[0057] Detailed Implementation
[0058] Example 1
[0059] (1) Preparation of polyoxymethylene-containing semi-solid polymer electrolyte
[0060] First, an ester electrolyte containing 2.0 wt% FEC in 1.0 M LiPF6 was prepared, with a DMC to EC volume ratio of 1:1. Then, trioxymethylene was added to the electrolyte, followed by 1.0 wt% epichlorohydrin. After thorough dissolution and homogenization, a clear and transparent polymerizable electrolyte solution containing 30.0 wt% trioxymethylene was obtained. The polymerizable solution was sealed and placed at 45°C for 10 hours to obtain a homogeneous, non-stratified white semi-solid polymer electrolyte containing polyoxymethylene.
[0061] The ionic conductivity of the ester electrolyte containing 2.0 wt% FEC was tested to be 5.3 mS / cm. -1 The polymerizable electrolyte solution containing 30.0 wt% paraformaldehyde has an ionic conductivity of 5.1 mS / cm. -1 The ionic conductivity of the polyoxymethylene-containing semi-solid polymer electrolyte is 4.9 mS / cm. -1 .
[0062] (2) Battery electrode manufacturing
[0063] a. Lithium manganese oxide cathode: After thoroughly grinding 92.0 wt% lithium manganese oxide and 5.0 wt% conductive carbon black, add 3.0 wt% PVDF (dissolved in NMP), continue grinding until uniform, then coat it onto the surface of aluminum foil current collector, and dry it in a 120℃ forced-air oven to obtain lithium manganese oxide cathode.
[0064] b. Graphite anode: After thoroughly grinding 85.0 wt% graphite carbon and 10.0 wt% conductive carbon black, add 3.5 wt% SBR and 2.5 wt% CMC (solvent is water), continue grinding until uniform, then coat it onto the surface of copper foil current collector, dry it in a 60℃ forced-air oven for 12 hours, and then dry it in a 120℃ forced-air oven to obtain the graphite anode.
[0065] (3) Battery assembly and performance characterization
[0066] The polymerizable electrolyte solution obtained in step (1) was prepared at a concentration of 4.2 g Ah. -1 The polyoxymethylene (POM) was added to a 1Ah pouch cell assembled by winding, using lithium manganese oxide as the positive electrode and graphite as the negative electrode. After vacuum settling and sealing, the internal resistance of the cell was measured to be 73.4 mΩ. The cell was then set at 25°C for 10 hours and at 45°C for 10 hours to allow trioxymethylene polymerization, followed by normal formation at 45°C. After a second sealing, a polyoxymethylene semi-solid-state lithium-ion battery was obtained, with an internal resistance of 75.1 mΩ. The polyoxymethylene content in the disassembled cell was approximately 3.2 wt%, and the increase in internal resistance was 2.7%.
[0067] The lithium manganese oxide lithium-ion batteries prepared by the above method were subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0068] Figure 1 Optical photographs of the polymerizable electrolyte solution and the polyoxymethylene-containing semi-solid polymer electrolyte of Example 1. From Figure 1 It can be seen that the polymerizable electrolyte solution is clear and transparent, while the polymerized paraformaldehyde becomes a white, non-flowing semi-solid with a uniform appearance, no stratification, and no obviously flowing liquid components, indicating that the liquid components are firmly bound in the polyformaldehyde matrix.
[0069] Example 2
[0070] (1) Preparation of polyoxymethylene-containing semi-solid polymer electrolyte
[0071] First, an ester electrolyte containing 2 wt% VEC and 2 wt% FEC (0.5 M LiFSI, 0.2 M LiBOB, and 0.5 M LiPF6) was prepared, with a volume ratio of DMC, EC, and EMC of 1:1:1. Then, trioxymethylene was added to the electrolyte, along with 1.0 wt% propyl ethylene oxide and 2.0 wt% 4-methyl-1,3-dioxolane. After thorough dissolution and homogenization, a clear and transparent polymerizable electrolyte solution containing 45.0 wt% trioxymethylene was obtained. The polymerizable electrolyte solution was sealed and placed at 60°C for 8 hours to obtain a homogeneous, non-stratified white semi-solid polymer electrolyte containing trioxymethylene.
[0072] The ionic conductivity of the ester electrolyte containing 2.0 wt% VEC and 2.0 wt% FEC was tested to be 6.7 mS / cm. -1 The polymerizable electrolyte solution containing 45.0 wt% paraformaldehyde has an ionic conductivity of 6.2 mS / cm. -1 The ionic conductivity of the polyoxymethylene-containing semi-solid polymer electrolyte is 1.7 mS / cm. -1 .
[0073] (2) Battery electrode manufacturing
[0074] a. NCM532 positive electrode: After thoroughly grinding 92.0 wt% NCM532 and 5.0 wt% conductive carbon black, add 3.0 wt% PVDF (dissolved in NMP), continue grinding until uniform, then coat it onto the surface of aluminum foil current collector, and dry it in a 120℃ forced-air oven to obtain the NCM532 positive electrode.
[0075] b. Graphite anode: After thoroughly grinding 85.0 wt% graphite carbon and 10.0 wt% conductive carbon black, add 3.5 wt% SBR and 2.5 wt% CMC (solvent is water), continue grinding until uniform, then coat it onto the surface of copper foil current collector, dry it in a 60℃ forced-air oven for 12 hours, and then dry it in a 120℃ forced-air oven to obtain the graphite anode.
[0076] (3) Battery assembly and performance characterization
[0077] The polymerizable electrolyte solution obtained in step (1) is prepared at a concentration of 3.0 g Ah. -1 The polyoxymethylene (POM) was added to a 3Ah pouch cell assembled using NCM532 as the positive electrode and graphite as the negative electrode via a stacking method. After vacuum settling and sealing, the cell's internal resistance was measured to be 7.5 mΩ. The cell was then set at 25°C for 24 hours and at 60°C for 8 hours to allow the polyoxymethylene to polymerize, followed by normal formation at 45°C. After a second sealing, a polyoxymethylene semi-solid-state lithium-ion battery was obtained, with an internal resistance of 7.8 mΩ. The polyoxymethylene content in the disassembled cell was approximately 6.8 wt%, resulting in an increase in internal resistance of 4.0%.
[0078] The NCM532 ternary soft-pack lithium-ion battery prepared by the above method was subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0079] Figure 2 (a) and (c) are electron microscope images of the positive electrode of the polyoxymethylene semi-solid lithium-ion battery after disassembly in Example 2; Figure 2 Images (b) and (d) are electron microscope (EM) images of the negative electrode of the polyoxymethylene (POM) semi-solid sodium-ion battery in Example 2 after disassembly. The EEM images show that the surfaces of both the positive and negative electrodes are covered with clusters of petal-shaped POM, and the cross-sections also reveal porous POM flakes penetrating deep into the pores of the electrode material.
[0080] Figure 3 This is an electron microscope (EM) image of the separator surface after disassembly of the polyoxymethylene (POM) semi-solid lithium-ion battery in Example 2. The EEM image shows that the separator surface is covered with a layer of continuous, petal-shaped POM with a porous structure.
[0081] Example 3
[0082] (1) Preparation of polyoxymethylene-containing semi-solid polymer electrolyte
[0083] First, an ester electrolyte containing 1.0 wt% PS and 3.0 wt% FEC, consisting of 0.5 M LiPF6, 0.2 M LiDFOB, and 0.3 M LiFSI, was prepared, with a volume ratio of DMC, EC, and DEC of 1:1:1. Then, trioxymethylene was added to the electrolyte, along with 1.0 wt% DOL and 2.0 wt% vinylcyclohexene dioxide. After thorough dissolution and homogenization, a clear and transparent polymerizable electrolyte solution containing 15.0 wt% trioxymethylene was obtained. The polymerizable electrolyte solution was sealed and placed at 45°C for 20 hours to obtain a homogeneous, non-stratified white semi-solid polymer electrolyte containing trioxymethylene.
[0084] The ionic conductivity of the ester electrolyte containing 1.0 wt% PS and 3.0 wt% FEC was tested to be 8.3 mS / cm. -1 The polymerizable electrolyte solution containing 15.0 wt% paraformaldehyde has an ionic conductivity of 8.2 mS / cm. -1 The ionic conductivity of the polyoxymethylene-containing semi-solid polymer electrolyte is 8.0 mS / cm. -1 .
[0085] (2) Battery electrode manufacturing
[0086] a. NCM622 positive electrode: After thoroughly grinding 92.0 wt% NCM622 and 5.0 wt% conductive carbon black, add 3.0 wt% PVDF (dissolved in NMP), continue grinding until uniform, then coat it onto the surface of aluminum foil current collector, and dry it in a 120℃ forced-air oven to obtain the NCM622 positive electrode.
[0087] b. Silicon-carbon composite anode: After thoroughly grinding 85.0 wt% composite silicon-carbon and 10.0 wt% conductive carbon black evenly, add 3.5 wt% SBR and 2.5 wt% CMC (solvent is water), continue grinding until uniform, then coat it onto the surface of copper foil current collector, dry it in a 60℃ forced-air oven for 12 hours, and then dry it in a 120℃ forced-air oven to obtain silicon-carbon composite anode.
[0088] (3) Battery manufacturing
[0089] The polymerizable electrolyte solution obtained in step (1) is prepared at a concentration of 3.0 g Ah. -1 The polyoxymethylene (POM) was added to a 2Ah pouch cell assembled using NCM622 as the positive electrode and silicon-carbon composite as the negative electrode via a stacking method. After vacuum settling and sealing, the internal resistance of the cell before polymerization was measured to be 6.8 mΩ. The cell was then set at 25°C for 24 hours and at 45°C for 20 hours to allow the POM to polymerize, followed by normal formation at 45°C. After a second sealing, a POM semi-solid-state lithium-ion battery was obtained, with an internal resistance of 6.9 mΩ. The POM content in the disassembled cell was approximately 1.3 wt%, and the increase in internal resistance was 1.5%.
[0090] The NCM622 ternary soft-pack lithium-ion battery prepared by the above method was subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0091] Example 4
[0092] (1) Preparation of polyoxymethylene-containing semi-solid polymer electrolyte
[0093] First, an ester electrolyte containing 1.0 wt% PS and 2.0 wt% VEC, consisting of 0.2 M LiPO₂F₂, 0.2 M LiDFOB, and 0.6 M LiFSI, was prepared, with a volume ratio of DMC, EC, and DEC of 1:1:1. Then, trioxymethylene was added to the electrolyte, along with 3.0 wt% trioxymethylene glycol glycidyl ether and 2.0 wt% PO. After thorough dissolution and mixing, a clear and transparent polymerizable electrolyte solution containing 20.0 wt% trioxymethylene was obtained. The polymerizable electrolyte solution was sealed and placed at 55°C for 8 hours to obtain a homogeneous, non-stratified white semi-solid polymer electrolyte containing trioxymethylene.
[0094] The ionic conductivity of the ester electrolyte containing 1.0 wt% PS and 2.0 wt% VEC was tested to be 7.2 mS / cm. -1 The polymerizable electrolyte solution containing 20.0 wt% paraformaldehyde has an ionic conductivity of 7.2 mS / cm. -1 The ionic conductivity of the polyoxymethylene-containing semi-solid polymer electrolyte is 7.1 mS / cm. -1 .
[0095] (2) Battery electrode manufacturing
[0096] a. Lithium iron phosphate cathode: After thoroughly grinding 92.0 wt% lithium iron phosphate and 5.0 wt% conductive carbon black, add 3.0 wt% PVDF (dissolved in NMP), continue grinding until uniform, then coat it onto the surface of aluminum foil current collector, and dry it in a 120°C forced-air oven to obtain lithium iron phosphate cathode.
[0097] b. Graphite anode: After thoroughly grinding 85.0 wt% graphite carbon and 10.0 wt% conductive carbon black, add 3.5 wt% SBR and 2.5 wt% CMC (solvent is water), continue grinding until uniform, then coat it onto the surface of copper foil current collector, dry it in a 60℃ forced-air oven for 12 hours, and then dry it in a 120℃ forced-air oven to obtain the graphite anode.
[0098] (3) Battery manufacturing
[0099] The polymerizable electrolyte solution obtained in step (1) is prepared at a concentration of 6.0 g Ah. -1 The polyoxymethylene (POM) was added to a 5Ah pouch cell assembled using lithium iron phosphate as the positive electrode and graphite carbon as the negative electrode. After vacuum settling and sealing, the internal resistance of the cell before polymerization was measured to be 9.6 mΩ. The cell was then set at 25°C for 24 h and at 55°C for 8 h to allow the POM to polymerize, followed by normal formation. After a second sealing, a POM semi-solid-state lithium-ion battery was obtained, with an internal resistance of 9.3 mΩ. The POM content in the disassembled cell was approximately 5.2 wt%, and the increase in internal resistance was 3.1%.
[0100] The lithium iron phosphate pouch lithium-ion batteries prepared using the above method were subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0101] Example 5
[0102] (1) The preparation of the polyoxymethylene semi-solid polymer electrolyte is the same as in Example 4, except that the concentration of trioxymethylene in the polymerizable electrolyte solution is 30.0 wt%.
[0103] (2) The manufacturing of the battery electrode is the same as in Example 4.
[0104] (3) Battery manufacturing
[0105] Following the steps of Example 4, a 5Ah pouch cell was assembled. The internal resistance of the cell before polymerization was 11.4mΩ, and the internal resistance of the polyoxymethylene semi-solid lithium-ion battery obtained after secondary sealing was 11.7mΩ. The content of polyoxymethylene in the disassembled cell was approximately 6.6wt%, and the increase in internal resistance was 2.6%.
[0106] The lithium iron phosphate pouch lithium-ion batteries prepared using the above method were subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0107] Example 6
[0108] (1) The preparation of the polyoxymethylene semi-solid polymer electrolyte is the same as in Example 4, except that the concentration of trioxymethylene in the polymerizable electrolyte solution is 40.0 wt%.
[0109] (2) The manufacturing of the battery electrode is the same as in Example 4.
[0110] (3) Battery manufacturing
[0111] Following the steps in Example 4, a 5Ah pouch cell was assembled. The internal resistance of the cell before polymerization was 12.3 mΩ, and after secondary sealing, the internal resistance of the polyoxymethylene semi-solid lithium-ion battery was 13.1 mΩ. The content of polyoxymethylene in the disassembled cell was approximately 7.1 wt%, with an increase in internal resistance of 6.5%.
[0112] The lithium iron phosphate pouch lithium-ion batteries prepared using the above method were subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0113] Example 7
[0114] (1) The preparation of the polyoxymethylene semi-solid polymer electrolyte is the same as in Example 4, except that the concentration of trioxymethylene in the polymerizable electrolyte solution is 45.0 wt%.
[0115] (2) The manufacturing of the battery electrode is the same as in Example 4.
[0116] (3) Battery manufacturing
[0117] Following the steps in Example 4, a 5Ah pouch cell was assembled. The internal resistance of the cell before polymerization was 13.2 mΩ, and after secondary sealing, the internal resistance of the polyoxymethylene semi-solid lithium-ion battery was 14.1 mΩ. The content of polyoxymethylene in the disassembled cell was approximately 7.5 wt%, with an increase in internal resistance of 6.8%.
[0118] The lithium iron phosphate pouch lithium-ion batteries prepared using the above method were subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0119] Compare with Example 1
[0120] (1) Preparation of electrolyte
[0121] Prepare the same ester electrolyte as in Example 2, containing 2 wt% VEC and 2 wt% FEC, consisting of 0.5 M LiFSI, 0.2 M LiBOB, and 0.5 M LiPF6, with a volume ratio of DMC, EC, and EMC of 1:1:1.
[0122] (2) The battery electrode is manufactured in the same way as in Example 2.
[0123] (3) Battery manufacturing
[0124] The electrolyte obtained in step (1) is prepared at a concentration of 3.0 g Ah. -1 The NCM532 ternary soft-pack battery, assembled in a stacked manner with NCM532 as the positive electrode and graphite as the negative electrode, was added to the same 3Ah soft-pack battery as in Example 2. After vacuum settling and sealing, the internal resistance of the cell was measured to be 7.7mΩ. After settling at room temperature (25°C) for 24 hours, formation was performed at 45°C, followed by a second sealing, resulting in a conventional liquid lithium-ion battery with an internal resistance of 7.7mΩ. The NCM532 ternary soft-pack battery was subjected to charge-discharge cycles at 25°C, and the battery performance results are shown in Table 1.
[0125] Figure 4 The first charge-discharge curves of the polyoxymethylene semi-solid lithium-ion battery prepared in Example 2 and the ordinary liquid lithium-ion battery in Comparative Example 1 are shown. The first charge-discharge curves of the two batteries show that their charge-discharge plateaus and capacities are similar, indicating that the polymer electrolyte containing polyoxymethylene is electrochemically stable within the battery's operating voltage range and does not introduce additional side reactions.
[0126] Figure 5 The graph shows the cycle performance results of the polyoxymethylene semi-solid lithium-ion battery prepared in Example 2 and the ordinary liquid lithium-ion battery in Comparative Example 1. As can be seen from the graph, after 1200 cycles at 1.0C, the capacity of the polyoxymethylene semi-solid lithium-ion battery prepared in Example 2 is 2796 mAh, while the capacity of the ordinary liquid lithium-ion battery in Comparative Example 1 is 2783 mAh. In terms of long-term cycle performance, the capacity of the polyoxymethylene semi-solid lithium-ion battery is slightly higher than that of the ordinary liquid lithium-ion battery, indicating that the semi-solid polymer electrolyte containing polyoxymethylene helps to improve the long-term cycle stability of the battery.
[0127] The performance results of the batteries prepared in Examples 1-7 and Comparative Example 1 are shown in Table 1 below.
[0128] Table 1 Performance parameters of batteries in Examples 1-7 and Comparative Example 1
[0129]
[0130] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a polyoxymethylene semi-solid lithium-ion battery, characterized in that, The method includes injecting a polymerizable electrolyte into the cell of a lithium-ion battery to prepare the polyoxymethylene semi-solid lithium-ion battery. The polymerizable electrolyte is composed of lithium electrolyte salt, electrolyte solvent, trioxymethylene, electrolyte additives and polyoxymethylene stabilizer additives. The electrolyte lithium salt is one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiTFSI, LiFSI, LiBOB, LiPO2F2, and LiDFOB; The molar concentration of the electrolyte lithium salt in the polymerizable electrolyte is 0.5-2.0 mol / L (M). The electrolyte additive is at least one of vinylene carbonate (VEC) and fluoroethylene carbonate (FEC); The electrolyte additive is present in a content of 1.0-7.0 wt% in the polymerizable electrolyte. The electrolyte solvent is two or three of the following: ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The content of the trioxymethylene in the polymerizable electrolyte is 5.0-60.0 wt%; The polyoxymethylene stabilizing additive is at least one of dioxolane compounds, compounds with monoepoxy functional groups, and compounds with polyepoxy functional groups. The dioxolane compounds are selected from DOL and 4-methyl-1,3-dioxolane. The compounds with the monoepoxy functional group are selected from propylene oxide (PO), epichlorohydrin (ECH), epibromopropane, 1,2-epoxyhexane, propyl ethylene oxide, phenyl glycidyl ether, methyl 2,3-epoxypropionate, ethyl 2,3-epoxypropionate, benzyl glycidyl ether, and 2-biphenyl glycidyl ether. The compounds with the polyepoxy functional groups are selected from 1,2,7,8-diepoxyoctane, dicyclopentadiene epoxide, 1,5-hexadiene diepoxide, vinylcyclohexene dioxide, neopentyl glycol diglycidyl ether, ethylene glycol glycidyl ether, bisphenol A diglycidyl ether, glycerol triglycidyl ether, pentaerythritol glycidyl ether, and 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexyl carboxylate. The content of the polyoxymethylene stabilizing additive relative to trioxymethylene is 0.5-7.0 wt%; The cell of the polyoxymethylene semi-solid lithium-ion battery contains 0.5-10.0 wt% trioxymethylene.
2. The preparation method according to claim 1, characterized in that, The polymerizable electrolyte has an ionic conductivity of 3.0-12.0 mS / cm. -1 .
3. The preparation method according to claim 1, characterized in that, The electrolyte additive is present in a content of 3.0-5.0 wt% in the polymerizable electrolyte.
4. The preparation method according to any one of claims 1-3, characterized in that, The content of the trioxymethylene in the polymerizable electrolyte is 15.0-30.0 wt%.
5. The preparation method according to any one of claims 1-3, characterized in that, The content of the polyoxymethylene stabilizing additive relative to trioxymethylene is 1.0-4.0 wt%; And / or, the content of trioxymethylene is 1.5-6.0 wt%.
6. The preparation method according to any one of claims 1-3, characterized in that, The polyoxymethylene semi-solid lithium-ion battery also contains a positive electrode and a negative electrode.
7. The preparation method according to claim 6, characterized in that, The positive electrode uses one of the following active materials: transition metal oxide materials and conversion-type positive electrode materials.
8. The preparation method according to claim 7, characterized in that, The transition metal oxide material is selected from one, two or more of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary cathode, nickel-cobalt-aluminum ternary cathode, lithium manganese oxide, and lithium-rich manganese-based cathode. And / or, the conversion cathode material is selected from one or both of sulfur cathode and iron fluoride cathode.
9. The preparation method according to claim 6, characterized in that, The negative electrode uses carbon materials, non-carbon negative electrode materials, or a composite negative electrode of carbon and non-carbon materials.
10. The preparation method according to claim 9, characterized in that, The carbon material is natural graphite, artificial graphite, or mesophase carbon microspheres (MCMB); The non-carbon anode material is lithium titanate, silicon-based materials and their composites, nitrides, or tin-based materials. The composite negative electrode made of carbon material and non-carbon material is a composite negative electrode made of graphite doped with silicon or graphite doped with silicon suboxide.
Citation Information
Patent Citations
Gel with adjustable strength and / or transition temperature, and preparation method and applications thereof
CN108963333A